Classroom Evaluation of Online Quizzing and Concept Building Exercises Embedded in an Integrated Learning System. (July 2020) - Nevid, Jeffrey S.; Gordon, Alexander J.; Terjesen, Mark D.; Hicks, Ashley
The advent of the integrated learning system (ILS) offers instructors opportunities to provide students with feedback-enabled, interactive learning exercises as online supplements to assigned textbooks. Major college publishers are now bundling an ILS with many of their textbook offerings in undergraduate courses in psychology and other fields. We incorporated an ILS in two separate classes in introductory psychology and evaluated the learning benefits of requiring ILS quizzing and concept-building exercises embedded within the ILS. The two classes were taught by different instructors using the same textbook and course examinations. We incentivized use of these ILS resources by allocating a substantial portion of the student's grade to performance on online assignments. Our findings suggest potential learning benefits of requiring these ILS resources. As learning benefits were limited to students in the upper third of the class distribution, additional efforts may be needed to help poorer performing students utilize online resources more effectively.